ENHANCING BUSINESS RESILIENCE IN SMES: THE ROLE OF ADAPTIVE LEADERSHIP AND LEARNING VIA DIGITAL READINESS AND DYNAMIC CAPABILITIES - Hendra Wahyudi; Andre Dwijanto Witjaksono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study investigates how adaptive resilience and human capital regeneration contribute to strategic sustainability in SMEs, while examining the potential moderating role of institutional flexibility. The research addresses a critical gap in understanding the interplay between organizational capabilities and institutional environments in emerging market contexts. Employing a quantitative research design, data were collected from SMEs in East Java through comprehensive surveys. The analysis utilized Structural Equation Modeling to assess the hypothesized relationships between the key constructs while ensuring robust validity and reliability tests. The results demonstrate that both adaptive resilience and human capital regeneration positively influence strategic sustainability. Contrary to expectations, institutional flexibility does not significantly moderate these relationships, suggesting that internal organizational capabilities may play a more pivotal role than external institutional factors in driving SME sustainability. This study offers novel theoretical insights by challenging conventional assumptions about institutional support in emerging markets. It contributes to the dynamic capabilities literature by highlighting the primacy of internal resilience and human capital development over institutional adaptability for SME sustainability.